Comparative safety of high-dose versus standard-dose influenza vaccination in patients with end-stage renal disease. Issue 33 (14th July 2020) - Layton, J. Bradley; McGrath, Leah J.; Sahrmann, John M.; Ma, Yinjiao; Dharnidharka, Vikas R.; O'Neil, Caroline; Weber, David J.; Butler, Anne M.
Highlights: Use of high-dose influenza vaccine is increasing among patients receiving dialysis. There were more minor events after high-dose vaccine than standard-dose vaccines. Serious events were rare and similar between high-dose and standard-dose vaccines. Abstract: Background: High-dose influenza vaccine (HDV) is an alternative vaccination strategy in patients with end-stage renal disease (ESRD), though the safety of HDV has not been evaluated in this population. The objective of this study was to estimate the relative occurrence of adverse vaccine reactions in patients with ESRD following vaccination with HDV compared with standard-dose influenza vaccine (SDV). Methods: Using data from the United States Renal Data System, we identified patients with ESRD aged ≥ 65 years at influenza vaccination during yearly influenza seasons from 2010 through 2016. Patients were followed after vaccination to observe serious (anaphylaxis, angioedema, seizure, encephalopathy, Guillain-Barré syndrome [GBS], and short-term, all-cause mortality) and milder (urticaria/hives, rash, pain in limb, cellulitis, myalgia/myositis, fever, nausea and vomiting, diarrhea, and syncope) adverse events. Propensity score-weighted hazard ratios (HRs) and 95% confidence intervals (CIs) for HDV versus SDV were estimated with Cox proportional hazards models. Results: Of 520, 876 vaccinations observed (mean age = 74.7 years at vaccination; 63% white race), 7.4% were HDV. For serious events, the weighted HRs were null for seizure, encephalopathy, and mortality and inestimable due to too few cases for anaphylaxis, angioedema, and GBS. For milder vaccine reactions, the weighted HRs demonstrated generally increased risks in the HDV group, including rash (HR = 1.86; 95% CI, 1.34–2.57), diarrhea (HR = 1.26; 95% CI, 1.07–1.50), pain in limb (HR = 1.23; 95% CI, 1.12–1.34), and myalgia/myositis (HR = 1.16; 95% CI, 1.04–1.30). Conclusions: The risks of serious adverse events were low and similar between treatment groups; however, HDV recipients had increased risks of several milder adverse events compared with SDV recipients, consistent with clinical trial findings in the general population of older adults. These results add important information to inform the risk-benefit tradeoff of the use of HDV versus SDV in patients with ESRD.